Mythen in nachmythischer Zeit: Die Antike in der deutschsprachigen Literatur der Gegenwart - Seidensticker, Bernd; Vöhler, Martin (De Gruyter, 2012)
Biographical note: Bernd Seidensticker holds a Chair in Classics at the Free University of Berlin. Martin Vöhler is a researcher working on the DFG-funded project on the "Reception of Classical Antiquity in present-day literature written in German.